A new budget allocation framework for selecting top simulated designs. Issue 9 (1st September 2016) - Gao, Siyang; Chen, Weiwei
ABSTRACT: In this article, the problem of selecting an optimal subset from a finite set of simulated designs is considered. Given the total simulation budget constraint, the selection problem aims to maximize the Probability of Correct Selection (PCS) of the top m designs. To simplify the complexity of the PCS, an approximated probability measure is developed and an asymptotically optimal solution of the resulting problem is derived. A subset selection procedure, which is easy to implement in practice, is then designed. More important, we provide some useful insights on characterizing an efficient subset selection rule and how it can be achieved by adjusting the simulation budgets allocated to all of the designs.